KONSOLIDASI SEBAGAI ALTERNATIF PENYEDIAAN TANAH UNTUK PEMBANGUNAN SARANA DAN FASILITAS UMUM - Bustomi, Abuyazid; Barhamudin, Barhamudin (Solusi, 2020)
The politics of consolidation is done to help the community in their efforts to make the area orderly and orderly, and the involvement of the government is very dominant. Land consolidation in Indonesia is aimed at slums or border areas or residential areas. The initiative to carry out land consolidation comes from the government, but it can also come from private companies. This research method is normative / literature, which is to get data from literature, books and legislation. The results of the study that the consolidation of land carried out to strengthen the value and function of the soil as a result of the arrangement of the shape, area, and location so that it becomes orderly and orderly that supports land use effectively and efficiently according to its potential. The obstacles if there are people who object to the consolidation of land for the development of public interests and public facilities. Obstacles from landowners in land consolidation, namely the difficulty of obtaining approval or agreement from landowners in land consolidation because the landowners' approval determines the issuance of a Regent / Mayor's decree on determining the location of land consolidation. The obstacle of the regional government in land consolidation is limited authority because the limitation of land rights is not the authority of the Regent / Mayor.